"Lean in": the moderating effect of female ownership on the relationship between human capital and organizational innovation. Issue 4 (25th July 2020) - Fu, Yanli; Liu, Ruiming; Yang, Jifeng; Jiao, Hao; Jin, Yuke
Abstract : Purpose: With the aim of shedding new light on the characteristics of human capital in its relationship with organizational innovation, this paper develops a novel theoretical and empirical exploration of the characteristics of human capital, both executives' experience and employees' average education level, as well as the moderating effect of female ownership, on two different aspects of organizational innovation. Design/methodology/approach: Data were obtained from the World Bank's China private manufacturing enterprise questionnaire survey. The study employs regression analysis of a logistic model using 1, 598 samples, because the dependent variable of an organization's innovation index is a binary variable. Findings: Using World Bank survey data of Chinese private manufacturing enterprises, the authors find that executives' experience has a significantly positive effect on process innovation. Female ownership strengthens the relationship between executives' experience and process innovation. Moreover, the results indicate that employees' average educational level has a significantly positive effect on product innovation. Female ownership strengthens the relationships between employees' average educational level and organizational innovation including product innovation and process innovation. This study highlights the importance of simultaneously testing the effects of human capital and gender heterogeneity on organizational innovation activities. Originality/value: This study explores the impact of human capital on organizational innovation activities in the context of the Chinese manufacturing industry. Moreover, organizational innovation activities are divided into two aspects: product innovation and process innovation. This study separately discusses the effect of human capital on these two kinds of innovation in detail. Finally, female ownership is selected as a moderating variable, and it is demonstrated that interactions of female owners with executives' experience and employees' average educational level have a positive impact on increasing different kinds of organizational innovation. The authors identify new boundary conditions for the domain of female research that are sorely lacking in the present literature.